Media Digital Literacy Program in Improving Parental Mediation Efficacy with Community Nursing Approach - Hani, Umi; Sonhaji, Sonhaji; Anggraini, Clara Novita (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The research started with initial screening by filling out a questionnaire on gadgets usage for elementary students. The treatment group (n=35) enrolled in 4 online meeting sessions with seven respondents per small group. In the same research period, the control group (n=35) enrolled in only one big class session about parental mediation. After the intervention, the sample measured the level of maternal self-efficacy. Univariate statistics determined the respondent’s characteristics, parental mediation of the use of gadgets in children, and the mother’s self-efficacy in parental mediation before and after the program. The data were not normally distributed using the Shapiro Wilk test. Thus differences in maternal self-efficacy before and after treatment were analyzed using Wilcoxon. Simultaneously, differences in self-efficacy between the treatment group and the control group were analyzed using Mann Whitney. Digital media literacy significantly increased mothers’ self-efficacy in mediating the use of gadgets by children (p <0.05)